Histopathological spectrum of breast lesions at B.P Koirala Memorial Cancer Hospital - Pandey, Greta; Rana, Asmita; Bhatta, Ranjan Raj; Upreti, Suraj; Jha, Nandita; Dhungana, Ishan (Nepalese Journal of Cancer, 2022)
Background: Breast lumps are the commonest presentation in surgical outpatient clinics in females. Breast is a complex organ structure. It shows a wide range of pathologies from benign inflammatory lesions to invasive life threatening lesions. Breast cancer has become the commonest cancer in females after cervix cancer also in Nepal. Modern diagnostic facilities have helped a lot for early detection of breast lesions and treatment. The present study was conducted at a tertiary cancer center in Nepal that focused on the identification of histopathological spectrum of breast biopsies received and their relations with epidemiological variables. Methods: This is a retrospective study of all the breast biopsies which were received, processed and analysed at Department of Pathology at B.P. Koirala Memorial Cancer Hospital from January to December 2019. The data were retrieved from the Department of Pathology. They were entered in Microsoft excel. Results: A total 216 breast tissues specimen of true-cut biopsy and lumpectomy were examined in the year 2019. The age range was from 18-75 years. There were 37.1% benign cases and 62.9% of malignant. There were 7 male patients in this study. Most of the cases belonged to age group of 40-49 years. Conclusion: This study shows the burden of breast cancer in Nepal. It also highlights the importance of histopathology in breast lesions not only in diagnosing the lesion but also in predicting the prognosis. Malignant lesions of breast were frequent in this study due to our center being a cancer referral hospital. This retrospective study shows that a variety of lesions are encountered in breast and histopathology helps to differentiate between various benign and malignant lesions.